Variables determining the development of colistin-associated renal impairment - CEYLAN, Bahadir; TANIS, Mudur; Akkoyunlu, MUHAMMED EMİN; AKKOYUNLU, MUHAMMED EMİN; CINAR, Ahmet; KURT, Ayse Ruhkar; Akkoyunlu, YASEMİN; AKKOYUNLU, YASEMİN; Ozkan, DİDEM; ÖZKAN, DİDEM; OZCELIK, Hatice Kutbay; ASLAN, Turan; et al. (My University, 2016)
The aim of this study was to identify the predictors of acute renal injury associated with colistin treatment.